Socio-Institutional Drivers of Groundwater Contamination Hazards: The Case of On-Site Sanitation in the Bwaise Informal Settlement, Kampala, Uganda - Felix R. B, Twinomucunguzi; Giorgia, Silvestri; Joel, Kinobe; Allan, Mugabi; Jenifer, Isoke; Philip, M. Nyenje; Jan Willem, Foppen; Robinah N, Kulabako; Frank, Kansiime (MDPI AG, 2021)
Socio-institutional factors are poorly addressed in the risk assessment of groundwater contamination. This paper contributes to the development of a socio-institutional assessment framework based on a case study of contamination by on-site sanitation (OSS) in an informal settlement of Bwaise (Kampala, Uganda). We conducted a snapshot survey of the recent extent of groundwater contamination by OSS using microbial and hydro-chemical indicators. Through transition arenas and key informant interviews, we investigated the socio-institutional drivers of the contamination. Overall, 14 out of the 17 sampled groundwater sources tested positive for Escherichia coli during the wet season. Nitrate concentrations at four sources exceeded the World Health Organization guideline value (50 mg/L), attributed to OSS. Despite the high contamination, the community highly valued groundwater as an alternative to the intermittent municipal water supply. We deduced six drivers of groundwater contamination, including land-use management, user attributes, governance, infrastructure management, groundwater valuation, and the operating environment (“LUGIVE”). Qualitative indicators for each of the drivers were also construed, and their interlinkages presented in a causal loop diagram, representing a socio-institutional assessment framework. The framework can help policymakers and the community to analyze various socio-institutional control levers to reduce the risk of groundwater contamination by OSS in informal settlements.
Keywords: contamination; groundwater; informal settlements; on-site sanitation; socio-hydrogeological systems